ANALISA KERUSAKAN PISTON MESIN DIESEL POMPA BANJIR DAN OPTIMASI SISTEM MANAJEMEN PEMELIHARAAN - Mochamad Sugiri; D. N. Adnyana; Agus Sugiana (Institut Sains dan Teknologi Nasional, 2022)
ABSTRACT To overcome the floods in Jakarta, DKI Jakarta's Water Resources Service alerted 144 (one hundred forty-four) pump houses that crossed the Ciliwung River. In addition to alerting the pump houses, DKI Jakarta also prepared 133 (one hundred thirty-three) portable (mobile) pumps spread over 5 (five) administrative cities. From the information obtained it is known that in January 2018 there was damage to the 1103 Series diesel engine piston, 50 kVA Generator drive, 36 kW operating in the Jakarta flood pump. Identified factors causing failure are preceded by a high-temperature indication on the cylinder wall which causes the piston to be stuck due to a lack of cylinder block lubrication. This study will identify the factors causing damage to the diesel engine flood pump in West Jakarta, analyze the failure of the piston engine diesel flood pump, determine precautionary measures, and determines maintenance techniques to avoid the same damage to the flood pump diesel engine piston, & analyzes the maintenance management system applied to the diesel engine. This study uses qualitative research methodology with the process of testing stages: macroscopic, metallographic, chemical composition analysis, hardness, SEM (Scanning Electron Macroscopy) which is equipped with EDXS (Energy Dispersive X-ray Spectroscopy) analysis, Schedule Oil Sampling. From the results of the discussion, it was found that the factors causing the piston diesel engine failure to the flood pump were very influential, by testing: 1) metallography obtained by the piston microstructure in the form of aluminum dendrite which indicated that the piston had local melting which resulted in local overheating; 2). viscosity (viscosity) of used oil is obtained: TBN (Total Base Number) on oil is a little low, oxidation is slightly above normal because of incomplete combustion, and there is an increase (difference) in the elements of Fe and Cu in used oil that is 9 ppm and 3 ppm, where if the Fe> content will cause damage to the Cylinder Block Liner & piston & if Cu> will cause failure to the bearing. From the results of this research, it is necessary to optimize the maintenance management system, namely: 1) implementing a Standard Operation Procedure for diesel engines (Inspection: fuel, radiator water, ACCU water, engine oil, R-S-T-N cable, ACCU cable, etc.); 2). perform predictive maintenance of diesel engine components (System maintenance: fuel flow, lubrication, air intake, and exhaust, cooling, starting system); 3). do preposterous maintenance (inspection: daily, 250, 500, 1000, 2000, 3000, 4000, 6000, 8000 and 12000 hours). Keywords: Failure, Pumps, Diesel Engines, Piston, Viscosity, Maintenance Management. Keywords: Centrifugal casting, tube reformer HP modified, creep test, Larson Miller parameter, remaining life assessment.